Effect of cycle numbers on the structural, linear and nonlinear optical properties in Fe2O3 thin films deposited by SILAR method - Erken, Ozge (Current applied physics, 2022)
Fe2O3 thin films were deposited by Successive Ionic Layer Adsorption and Reaction (SILAR) method onto glass substrates at different cycle numbers to investigate structural, linear and nonlinear optical properties. X-Ray Diffraction (XRD) analysis revealed that the Fe2O3 thin films have a non-crystalline nature. The morphological properties of the films were investigated by Field Emission-Scanning Electron Microscopy (FE-SEM) and the results show that the films’ surfaces are porous. The linear and nonlinear optical parameters were evaluated and analyzed by using transmittance and absorbance measurements. For these measurements, UV–Vis spectroscopy at room temperature was used. The refractive index values were calculated in the range of 1.45–3.23 for visible region (400–700 nm). Obtained results reveal that direct optical band gap changed between 2.62 and 2.68 eV and indirect optical band gap changed between 1.67 and 1.77 eV. Additionally, optical electronegativity, optical dielectric constants, surface and volume energy loss functions, nonlinear refractive index, linear optical susceptibility, third-order nonlinear optical susceptibility, optical and electrical conductivity, and loss tangent values were calculated and discussed in detail. It was found that each parameter studied is dependent on the cycle numbers. Also, it can be stated that Fe2O3 thin films are promising candidate for solar cells and optoelectronic device technology. Figure The change of a) linear optical susceptibility and b) third order nonlinear optical susceptibility values as function of wavelength for Fe2O3 thin films. It can be seen from Fig. 14(a) that the linear optical susceptibility (χ(1)) values of Fe2O3 thin films changed in the range of 0.088–0.753 in the visible region. It starts to decrease in the wavelength range of 400–600 nm and become stable at higher values of 600 nm. On the other hand, χ(1) values decrease with increasing the cycle numbers. Moreover the third order nonlinear optical susceptibility (χ(3)) values are in the range of 1.047 × 10−11–5.474 × 10−8 esu in the visible region. This value decreases sharply in the 400–500 nm wavelength range and are almost constant at wavelengths higher than 500 nm. These values support usage of F2O3 thin films for optoelectronic device and solar cell technologies. [Display omitted] •Fe2O3 thin films were fabricated successfully by Successive Ionic Layer Adsorption and Reaction (SILAR) method onto glass substrates.•Refractive index and other optical parameters were determined.•Direct and indirect optical band gap was calculated using the Tauc plot.•Linear optical susceptibility, third-order nonlinear optical susceptibility and nonlinear refractive index were calculated.•The physical and optical properties indicated strong dependence on cycle number.